ANALISIS SEKTOR TERTINGGAL KABUPATEN SAMOSIR DENGAN METODE LOCATION QUOTIENT - Rizki Kurniawan; Ahmad Syukron Prasaja (Pusat Riset dan Publikasi, 2023)
This study aim to improve the economic performance of a country, the growth of Gross Regional Domestic Product (GDP) from various industries can be utilized. Regional Gross Domestic Product (GRDP) is a factor that can be used to determine the level of a country's or region's economy either at current prices or constant prices. This Gross Regional Domestic Product (GDP) growth occurs if the area has a leading sector or a base sector with a relatively fast growth rate. This study uses time series data from the Central Bureau of Statistics (BPS) for North Sumatra Province for 2018 and 2021. The purpose of this study is to identify leading, lagging, developing sectors and potential business fields from the Samosir Regency area in 2018 to 2021. 2018 was taken before it happened. The Covid-19 pandemic and the year 2021 are taken after the events of Covid-19. This is done using the location quotient analysis method and the dynamic location quotient (DLQ) method.